Answer:
x=3, Y= 4
Explanation:
① Label the 2 equations
Y= ⅓x +3 -----(1)
Y= 2x -2 -----(2)
② Since both equations are Y= ____, substitute one equation into the other so that we are left with x terms and constant only.
subst. (1) into (2):
⅓x +3= 2x -2
③ Bring x terms to one side and constants to the other.
2x -⅓x= 3 +2
simplify:
![(5)/(3) x = 5](https://img.qammunity.org/2021/formulas/mathematics/college/xq7cc34bneo79awvdnd7be87vh01b600tg.png)
![x = 5 / (5)/(3) \\ x = 5 * (3)/(5) \\ x = 3](https://img.qammunity.org/2021/formulas/mathematics/college/hjh76j2pv2wm9perl16fdevq0ja6s6t7b3.png)
④ Solve for y.
Subst. x=3 into (2):
Y= 2(3) -2
Y= 6 -2
Y= 4